Answer: -694
Step-by-step explanation:
Let's assume we have to find [tex]f(9)+g(9)[/tex] with the given functions:
[tex]f(x)=2x-513[/tex] (1)
[tex]g(x)=3x-226[/tex] (2)
If we want to find [tex]f(9)[/tex] we have to substitute the [tex]x[/tex] by [tex]9[/tex]:
[tex]f(9)=2(9)-513[/tex]
[tex]f(9)=-495[/tex] (3)
If we want to find [tex]g(9)[/tex] we have to substitute the [tex]x[/tex] by [tex]9[/tex]:
[tex]g(9)=3(9)-226[/tex]
[tex]f(9)=-199[/tex] (4)
Finding [tex]f(9)+g(9)[/tex]:
[tex]f(9)+g(9)=-495+(-199)[/tex]
Finally:
[tex]f(9)+g(9)=-694[/tex]